LEGAL SANCTIONS FOR THE CRIMINAL ACT OF LAND CLAIMS IN A POSITIVE AND CRIMINAL LAW PERSPECTIVE ISLAMIC CRIMINAL LAW - Mhd. Ihwanuddin Hasibuan; Mark G. Maffett; Bob Feinbrg (Journal of International Islamic Law, Human Right and Public Policy, 2023)
The research aims to find out what the penalties are for perpetrators of criminal acts of land grabbing from a positive criminal law perspective and the penalties for perpetrators of criminal acts of land grabbing from a criminal law perspective. The type of research method used by normative juridical research. Secondary data sources were obtained from Al-Qur'an, Hadith, Fiqh Jinayah books, and the Criminal Code. Then it is analyzed using a qualitative descriptive method, namely explaining everything in the main issues firmly based on the problem formulation which is concluded inductively. Based on the results of the research, it can be concluded that the legal sanction for the crime of land grabbing according to the positive criminal law contained in the Criminal Code (KUHP) can be punished according to the provisions of article 385 by 4 years' imprisonment, whereas in Islamic criminal law the sanction of imprisonment can be imposed with the fingertips. ta'zir.